2014
DOI: 10.1002/jcb.24665
|View full text |Cite
|
Sign up to set email alerts
|

miR‐495 Enhances the Sensitivity of Non‐Small Cell Lung Cancer Cells to Platinum by Modulation of Copper‐Transporting P‐type Adenosine Triphosphatase A (ATP7A)

Abstract: Copper-transporting P-type adenosine triphosphatase A (ATP7A) is associated with platinum drug resistance in non-small cell lung cancer (NSCLC). microRNAs (miRNAs) are a class of small non-coding RNA molecules that regulate gene expression at post-transcriptional level. In this study, the aim is to explore which miRNAs might participate in the platinum resistance by targeting ATP7A in NSCLC. Using real-time PCR-based miRNA expression profiling and bioinformatics, we selected miR-495 as a candidate miRNA. EGFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 30 publications
0
45
0
1
Order By: Relevance
“…Lv et al found that restored miR-495 expression inhibits cell proliferation and motility and induces G0/G1 phase arrest in renal cell carcinoma (37). In lung cancer, miR-495 is involved in the regulation of cell proliferation, migration, epithelial-mesenchymal transition, chemosensitivity and chemoresistance (40,41,46). However, Tan et al indicated that miR-495 serves as an oncogene in bladder cancer through the regulation of cell proliferation and invasion (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lv et al found that restored miR-495 expression inhibits cell proliferation and motility and induces G0/G1 phase arrest in renal cell carcinoma (37). In lung cancer, miR-495 is involved in the regulation of cell proliferation, migration, epithelial-mesenchymal transition, chemosensitivity and chemoresistance (40,41,46). However, Tan et al indicated that miR-495 serves as an oncogene in bladder cancer through the regulation of cell proliferation and invasion (18).…”
Section: Discussionmentioning
confidence: 99%
“…The following target miR-495 genes have been identified: HMGN5 (19) in osteosarcoma; GFI1 (35) in medulloblastoma; Glut1 (42), MYB (43) and CDK6 (44) in glioma; FZD4 (36), Akt (45) and mTOR (45) in prostate cancer; SATB1 (37) in renal cell carcinoma; STAT-3 (38) and Bmi-1 (39) in breast cancer; epithelial and endothelial tyrosine kinase (40), MTA3 (41) and ATP7A (46) in lung cancer; and PTEN (18) in bladder cancer. In our study, IGF1R was demonstrated to be a direct functional downstream target of miR-495 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that continuous infusion or multiple administrations of CDDP often results in the development of drug resistance, which often leads to treatment failure as demonstrated by tumor growth or tumor relapse (38,39). Recently, studies have established that miRNAs are also involved in the development of chemoresistance (40)(41)(42). Our data indicate that decreased miR216a expression contributes to CDDP resistance in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer (NSCLC), hsa-miR-495 was found to inhibit the growth and migration of NSCLC by directly targeting MTA3 [37]. Moreover, hsa-miR-495 was also found to sensitize the NSCLC cells' response to drugs like cisplatin [38]. Jiang et al found hsa-miR-495 functions as a tumor suppressor in acute myeloid leukemia [39].…”
Section: Discussionmentioning
confidence: 99%